Dr. Jožica Gričar – prejemnica Zoisovega priznanja za pomembne dosežke na področju biologije dreves - Čufar, Katarina (Les (Ljubljana), 2026)
In November 2025, Dr Jožica Gričar received the Zois Award for her outstanding achievements in tree biology, the prestigious state award of the Republic of Slovenia. This article presents the scientific work and accomplishments of Dr Gričar, a scientific advisor at the Slovenian Forestry Institute. Specializing in wood and phloem research, she has made a substantial contribution to the global understanding of how stress influences the physiological processes in trees and their diameter growth. Through extensive international collaboration, her research has advanced knowledge of tree responses to changing environmental conditions, particularly through adaptive modifications in the development of tissues (wood and phloem) and organs (leaves, stems and roots), as reflected in their structure. In the context of climate change and increasingly frequent extreme weather events, her team’s findings published in leading scientific journals and presented to national and international audiences provide valuable guidance for selecting appropriate tree species and provenances for the restoration of disturbed and degraded ecosystems.
Keywords: biologija dreves; cambium; climate change; debelinska rast; diameter growth; državno priznanje; fenologija; floem; Gričar, Jožica; kambij; les; national award; phenology; phloem; podnebne spremembe; tree biology; wood